Pengembangan Wisata Budaya Wayang Wong di Desa Wisata JSPB Songgo Langit Mangunan - Tanto Lailam; Awang Daru Murti; Ani Yunita (J-ABDIPAMAS (Jurnal Pengabdian Kepada Masyarakat), 2021)
The community empowerment program is a “Program Pemberdayaan Desa Mitra” with the theme of Mangunan Village tourism for good tourism, competitive and cultured. The program focused on the development of traditional performance (puppet) / wayang wong as cultural tourism which is integrated with the natural exploration of Bowongan Agricultural rice fields, bowongan peaks, watu pipisan and traditional culinary "Sego Wiwit". The wayang wong cultural tourism development program is carried out by establishing the Ngesti Budoyo art studio (sanggar seni), conducting various development training (tourism institutions training, tourism packaging training, and cultural tourism marketing training). To support these activities, development facilitation the large billboards containing the potential of wayang wong as cultural tourism, and promotion of cultural tourism in various media, especially social media (Facebook, Instagram, youtube, and others). Program pemberdayaan masyarakat skema Program Pemberdayaan Desa Mitra yang mengangkat tema wisata Desa Mangunan yang unggul, kompetetif dan berbudaya. Program ini memfokuskan pada pengembangan wisata budaya wayang wong (wayang orang) yang diintegrasikan dengan wisata alam jelajah sawah pertanian bowongan, puncak bowongan, watu pipisan dan kuliner tradisonal sego wiwit. Program pengembangan wisata budaya wayang wong ini dilakukan dengan pembentukan sanggar kesenian Ngesti Budoyo dengan akta notaris, melakukan berbagai pelatihan pengembangan (kelembagaan desa wisata, pelatihan pemaketan, dan pelatihan pemasaran wisata budaya). Untuk mendukung kegiatan tersebut, fasilitasi pengembangan berupa pemasangan reklame besar berisi potensi wayang wong sebagai wisata budaya, dan promosi wisata budaya di berbagai media, terutama media sosial (facebook, instragram, youtube, dan lainnya)